A partilha do sensível como princípio fundamental da formação humana - Moreira, Jairo Barbosa (2022)
This thesis is linked to the research line "Educational Culture and Processes" of the Stricto Sensu Graduate Program in the Faculty of Education in the Federal University of Goiás (UFG). This is a theoretical, bibliographical research on the concept of distribution of the sensible in Jacques Rancière and its importance for human formation. In the track of Rancière's thought, the thesis aims to demonstrate the way in which the regimes of identification of art - ethical, representative-poetic, aesthetic - determine the formation of human beings in different times in history. What is defended in this work is the presupposition that all human formation must have as a principle the distribution of the sensible, that is, equality understood as an element of the esthetic regime. We argue in defense of the school, specifically the university, as an esthetic community whose objective is to insert humans into the collectivity universe, therefore, into the politics universe, making them emancipated subjects, capable for transforming the reality in which they belong find inserted. We also understand that an esthetic community takes place in a peculiar way through the constitution of readers community, because we understand literature as a plural art that enables the meeting of the sensitive and the intelligible through the free play of Reading. Reading is an act in which you give and receive at the same time; it is a distribution of the sensible, as "it is always a controversial distribution of ways of being and "occupations" in a space of possibles". (RANCIERE, 2014, p. 63). Reading is an act of provocation, questioning, revolt and subversion of the domination logic, because it sharpens imagination and curiosity. In order to do this, we went through the thought of some philosophers, among them Plato, Aristotle, Kant and Schiller, to arrive at the conception of esthetics in Rancière. For this author, the esthetic regime is a way of life, a way of doing, feeling, thinking and being in the world and with the world, therefore, human formation cannot be understood in a linear and dimensional perspective. Education is a multiplicity of acts and its objective is not just learning, by the way he believes that "thought has no place its own". In this sense, we defend the idea of a new humanism based on the principle of distribution of the sensible.